2000
DOI: 10.1046/j.1525-1411.2000.22007.x
|View full text |Cite
|
Sign up to set email alerts
|

PSP94: Evaluation of Prognostic Utility in Patients Treated with Radiotherapy for Nonmetastatic Prostate Cancer

Abstract: Objectives: Conflicting reports exist as to the utility of PSP94 in the diagnosis and management of prostate cancer. We have identified serum‐bound forms of PSP94 in prostate cancer patients. To further evaluate the usefulness of this finding, we measured bound and free serum PSP94 levels in patients with nonmetastatic prostate cancer before radiotherapy. Materials and Methods: Pretreatment levels of free PSP94 in 42 patients were measured in serum via a competitive enzyme‐linked immunosorbent assay. Levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…This study follows on from previous work in which a multistep biochemical test was used to assess the relative levels of bound and free PSP94 in the initial serum of localized prostate cancer patients subsequently treated with radiation (13). In that study, the ratio of bound PSP94 to free PSP94 was an independent predictor of time to biochemical recurrence.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…This study follows on from previous work in which a multistep biochemical test was used to assess the relative levels of bound and free PSP94 in the initial serum of localized prostate cancer patients subsequently treated with radiation (13). In that study, the ratio of bound PSP94 to free PSP94 was an independent predictor of time to biochemical recurrence.…”
Section: Discussionmentioning
confidence: 90%
“…More recently, PSP94 was found to circulate in low and high molecular weight forms, suggesting the presence of a high -molecular weight blood-binding factor (9,12). In the pretreatment serum of patients treated with radiation, it was shown that tests differentiating between the free and bound forms of PSP94 had significant and independent prognostic value adjusting for initial PSA and Gleason score (13). More recently, a serum protein with high binding affinity for PSP94 (14), facilitating the development of monoclonal antibodies and immunoassays that specifically recognize the free and total forms of PSP94.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[31][32][33] Serumfree and bound forms of PSP94 were identified 31 and a new differential test between free and bound forms of PSP94 showed an improved prognostic value. 31,34 Studies in human, primate, pig, rat and mouse PSP94 have shown that PSP94, unlike rPB and PSA, is a conserved, but rapidly evolving protein, for a mini-review see Ref. 35.…”
Section: Psp94 Gene Promoter/enhancer Region-directed Sv40 Tag Expresmentioning
confidence: 99%
“…Thus, investigators began to work towards identifying putative binding molecules of PSP94 that would enable development of serum immunoassays for PCa management by utilizing the bound and free forms of PSP94. Higher ratio of bound/free forms of serum PSP94 (sPSP94) compared to sPSA level in pretreatment samples was demonstrated to be a significant predictor of relapse post radiotherapy (110). Serum PSP94-bound complexes were later considered for evaluating the clinical utility of PSP94 as a marker for PCa progression.…”
Section: Structural Studies Of Psp94mentioning
confidence: 99%